Experimental Study on the Damage Characteristics of Polymer Slabs Subjected to Air Contact and Close-In Explosions. (26th July 2021) - Liu, Zhidong; Zhao, Xiaohua; Fang, Hongyuan; Du, Xueming; Xue, Binghan; Li, Zhaonan
Abstract : As a new antiseepage reinforcement material, polyurethane grouting material has been widely studied in terms of its static mechanical properties. However, research on its dynamic mechanical properties is relatively rare. In this research, considering the influence of the explosive charge weight, the air contact and close-in explosion experiments of polymer slabs were carried out. The failure mode and damage spatial distribution characteristics of polymer slabs were explored. Pressure time history curve of air shock wave was obtained using an air shock wave tester. The influence of polymer slabs on the propagation of air explosion shock wave was compared and analyzed. The results show that, under the air contact explosion, the polymer slab mainly suffers local damage, while under close-in explosion, overall damage is the main damage mode. With the increase of the explosive charge weight, the failure mode of the polymer slab transits from surface crack and slight spalling to local and whole crushing.